Nuclear Maturation of Porcine Oocytes in vitro: Effect of the Cumulus-Oocyte Complexes Quality - Ni Wayan Kurniani Karja (Indonesian Journal of Biotechnology, 2008)
The objective of this study was to examine the effect of the cumulus-oocyte complexes (COCs) quality on the ability of porcine oocytes to mature in vitro. Porcine COCs were collected from 2-6 mm follicles of slaughterhouse ovaries. The oocytes used for IVM were classified into three categories based on the compactness and transparency of the cumulus investment and homogeneity and transparency of the ooplasm. The oocytes were then matured in vitro for 44 h. At 22 of maturation culture, most of the oocytes in all groups were identified still at germinal vesicle (GV) stage and metaphase I (M-I) stage. After 44 h of culture, a greater proportion of Category I and II oocytes completed in vitro maturation through the second meiotic as compared with that of Category III oocytes (P<0.05). The proportion of oocytes remaining at M-I stage and the degenerative oocytes in Category III oocytes were significantly higher than those of oocytes in other groups (P<0.05). These data indicate that porcine oocytes with high quality cytoplasm and a cumulus cell complement have a much greater chance of maturing in vitro than that lower quality oocytes. The morphological grading of immature oocytes is an appropriate selection criterion for their developmental ability.